Correlation of serum trace elements (Fe, Cu, and Zn) in the blood samples of Indian patients with leukoplakia, oral squamous cell carcinoma, and normal subjects - Sourabh, Abhishek; Shreedhar, Balasundari; Khare, Abhishek; Haideri, Safia; Kalim, Shadab; Srivastava, Ankita (Journal of oral and maxillofacial pathology : JOMFP, 2023)
Context: Trace elements (iron, copper, and zinc), leukoplakia, and oral squamous cell carcinoma. Aims: To study and correlate serum trace element (iron, copper, and zinc) levels in leukoplakia, oral squamous cell carcinoma, and normal subjects. Settings and Design: The present study comprised a total of 80 patients, which included 30 patients of leukoplakia, 30 patients of oral squamous cell carcinoma, and the normal control group comprising 20 healthy individuals who were not having any relevant medical, dental, and habit history. Subjects and Methods: Peripheral blood samples of a volume of 10 ml each will be collected by anti-cubical vein puncture from control groups and from patients suffering from leukoplakia and oral squamous cell carcinoma. The blood will be collected in a plain red top vein puncture tube without additives or anti-coagulants and allowed to stand undisturbed to clot at room temperature, and serum will be separated from the cells by centrifugation at 4°C at a speed of 3000 rev/min, the separated sera will be kept at -20°C until analysis is performed. Estimation of Serum Iron, Zinc, and Copper Levels: The estimation of serum zinc (Zn) and copper (Cu) levels is performed by atomic absorption spectrometry (AAS). In the present study, the estimation of copper and zinc levels was conducted by using an atomic absorption spectrophotometer (model no: AA-6300 SHIMADZU, Japan). Serum iron estimation is performed using the kit RANDOX (siedel, 1984). Statistical Analysis Used: Statistical analysis is performed by the paired and Scheffe tests. Results: From the results, it was concluded that there was a decrease in serum iron and zinc levels and copper had increased serum levels. Conclusions: It was concluded that evaluation of serum trace elements can be a cost-effective and non-invasive alternative for screening, diagnosis, and monitoring of pre-malignant lesions such as leukoplakia and malignant lesions such as oral squamous cell carcinoma. Thus, these parameters can be used as biomarkers that provide important tools in formulating an adequate diagnosis, treatment plan, and prognosis for oral squamous cell carcinoma.